Treatment process for reducing sulfur content of calcined petroleum coke
By using a composite catalyst, combining rectorite, light calcium carbonate and mercaptosuccinic acid, and introducing a zirconium-aluminum coupling agent, the problem of difficulty in reducing the sulfur content during petroleum coke calcination is solved, and high-efficiency desulfurization and equipment life extension are achieved. Effect.
Patent Information
- Application Number
- CN202411570359.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The prior art is difficult to effectively reduce the sulfur content when calcining petroleum coke, resulting in a low desulfurization rate, and the calcining equipment is prone to corrosion and has a short service life.
The combination of composite catalysts is introduced through the combination of stones, calcium carbonate and cytoccitric acid, and introduced aluminum aluminum coupling agents to modify, forming a composite carrier with high -pore structure and composite surface area to improve the effect of oil focus.
The desulfurization rate of oil coke is significantly increased, the sulfur content is reduced, the service life of the burning equipment is prolonged, and the production cost is reduced.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of petroleum coke desulfurization technology and relates to a treatment process for reducing the sulfur content of calcined petroleum coke. Background Art
[0002] Petroleum coke is made of vacuum residue oil as the main raw material. It is mainly obtained by the cracking and carbonization of petroleum-derived raw materials such as catalytic cracking oil slurry, ethylene tar, refinery waste oil and scum in the overall material balance of the refinery during delayed coking or fluidized coking. Petroleum coke has a dense intrinsic structure, with carbon as the main element, and also contains other heteroatoms such as nitrogen, sulfur, iron, zinc, cadmium, etc. Petroleum coke can be divided into sponge coke (commonly used as fuel, reducing agent, negative electrode material and prebaked anode), shot coke (used for fuel), and needle coke (used for the production of graphite electrodes and lithium battery negative electrode raw materials) according to its appearance and properties. High-sulfur petroleum coke is usually used as fuel and for the preparation of low-value-added products such as reducing agents, while low-sulfur petroleum coke is mainly used for lithium battery negative electrode materials and prebaked anodes, and its added value is relatively high. In order to improve its utilization efficiency, petroleum coke needs to be desulfurized.
[0003] During the calcination process, the sulfides in petroleum coke are removed, and the calcined petroleum coke is called "cooked coke". In industry, the calcination temperature of petroleum coke is usually between 1100 and 1400 degrees Celsius. Within this temperature range, the desulfurization rate can reach about 50.0%. In this temperature range, the carbonaceous structure begins to rearrange; as the carbonaceous structure rearranges, the sulfides in the petroleum coke begin to be released. However, its calcination temperature is too high, and catalysts are often required to improve the desulfurization efficiency. The use of catalysts can reduce the decomposition temperature of sulfides, thereby achieving a higher desulfurization rate at a lower temperature. In addition, catalysts can promote the conversion of sulfides, reduce corrosion to calcination equipment, and extend the service life of equipment. When selecting a catalyst, its activity, selectivity, and stability to the calcination process need to be considered. By optimizing the type and amount of catalyst, the desulfurization effect of petroleum coke can be further improved while reducing production costs. Summary of the invention
[0004] The purpose of the present invention is to provide a treatment process for reducing the sulfur content of calcined petroleum coke. The composite catalyst prepared by the present invention is used for catalytic desulfurization of petroleum coke and has an excellent desulfurization effect.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A treatment process for reducing the sulfur content of calcined petroleum coke, the treatment process comprises the following steps: grinding the petroleum coke, screening it, adding a composite catalyst, mixing it, and then calcining it, and the process is completed after cooling.
[0006] As a preferred technical solution of the present invention, in the treatment process, the screening is through a 50-100 mesh sieve; the mixing time is 30-40 minutes; and the calcination treatment is calcination at 620-690° C. for 70-90 minutes.
[0007] The invention discloses a method for preparing the composite catalyst, comprising the following steps: Step 1): Grind and mix rectorite, light calcium carbonate and anhydrous ethanol, add mercaptosuccinic acid and stir to mix, add a coupling agent and mix well, then heat the mixture, filter out the solid, vacuum dry and calcine to obtain a composite carrier; Step 2): After mixing the composite carrier, ethylene glycol and deionized water, add nickel nitrate hexahydrate and ammonium molybdate tetrahydrate, add ammonia water, heat and stir, cool to room temperature and centrifuge, wash with ethanol solution for multiple times, vacuum dry and calcine to obtain a composite catalyst.
[0008] As a preferred technical solution of the present invention, in step 1), the grinding and mixing is performed at a rotation speed of 400-500 r / min for 40-60 min; and the stirring and mixing time is 40-50 min.
[0009] As a preferred technical solution of the present invention, in step 1), the vacuum drying is drying at 80°C to constant weight; the heating treatment is stirring at 50-60°C and 500-700 r / min for 4-5 hours.
[0010] As a preferred technical solution of the present invention, in step 1), the mass ratio of the rectorite, light calcium carbonate, mercaptosuccinic acid, anhydrous ethanol and coupling agent is (8-9): (0.06-0.08): (0.2-0.4): (30-35): (3.2-3.4).
[0011] As a preferred technical solution of the present invention, in step 1), the coupling agent is a zirconium-aluminum coupling agent; and the calcination is performed at a temperature of 500° C. for 3-4 hours.
[0012] As a preferred technical solution of the present invention, in step 2), the heating and stirring is heating at 200° C. for 2.0-2.5 hours; and the concentration of the ethanol solution is 70wt%.
[0013] As a preferred technical solution of the present invention, in step 2), the calcination is performed at a temperature of 400-420° C. for 1.0-1.2 h.
[0014] As a preferred technical solution of the present invention, in step 2), the mass ratio of the composite carrier, ethylene glycol, deionized water, nickel nitrate hexahydrate, ammonium molybdate tetrahydrate and ammonia water is 20-24:70-80:20-22:0.6-0.8:2.4-2.8:10-12; the concentration of the ammonia water is 24%.
[0015] Beneficial effects of the present invention: The present invention forms a composite by rectorite and calcium carbonate, then attaches mercaptosuccinic acid to the composite, and performs calcination activation after modification by grafting a zirconium-aluminum coupling agent, thereby significantly improving the pore structure and specific surface area of the composite carrier, and improving the adsorption capacity of active metal nickel / molybdenum. At the same time, the aluminum oxide / zirconium oxide layer can effectively increase the thermal stability of the rectorite, and reduce the collapse phenomenon that occurs during excessive calcination activation or calcination desulfurization. DETAILED DESCRIPTION
[0016] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0017] Example 1
[0018] A treatment process for reducing sulfur content of calcined petroleum coke comprises the following steps: grinding the petroleum coke, sieving it, adding a composite catalyst, mixing it, and then calcining it, and cooling it to room temperature; In the treatment process, the screening is through a 60-mesh sieve; the mixing time is 30 minutes; and the calcination treatment is calcination at 620° C. for 70 minutes.
[0019] The preparation method of the composite catalyst comprises the following steps: Step 1): Grind and mix rectorite, light calcium carbonate and anhydrous ethanol, add mercaptosuccinic acid and stir to mix, add a coupling agent and mix well, then heat the mixture, filter out the solid, vacuum dry and calcine to obtain a composite carrier; Step 2): After mixing the composite carrier, ethylene glycol and deionized water, add nickel nitrate hexahydrate and ammonium molybdate tetrahydrate, add ammonia water, heat and stir, cool to room temperature and centrifuge, wash three times with ethanol solution, vacuum dry and calcine to obtain a composite catalyst.
[0020] In step 1), the grinding and mixing is grinding at a speed of 400 r / min for 40 minutes; the stirring and mixing time is 40 minutes; the heating treatment is stirring at a temperature of 50°C and a speed of 500 r / min for 4 hours; the vacuum drying is drying at a temperature of 80°C to constant weight; the calcination is calcining at a temperature of 500°C for 3 hours; the mass ratio of the rectorite, light calcium carbonate, mercaptosuccinic acid, anhydrous ethanol and coupling agent is 8:0.06:0.2:30:3.2; and the coupling agent is a zirconium-aluminum coupling agent.
[0021] In step 2), the heating and stirring is heating at 200°C for 2.0h; the concentration of the ethanol solution is 70wt%; the calcination is calcining at 400°C for 1.0h; the mass ratio of the composite carrier, ethylene glycol, deionized water, nickel nitrate hexahydrate, ammonium molybdate tetrahydrate and ammonia water is 20:70:20:0.6:2.4:10; the concentration of the ammonia water is 24%.
[0022] Example 2
[0023] A treatment process for reducing sulfur content of calcined petroleum coke comprises the following steps: grinding the petroleum coke, sieving it, adding a composite catalyst, mixing it, and then calcining it at high temperature, and then cooling it to room temperature; In the treatment process, the screening is through a 60-mesh sieve; the mixing time is 32 minutes; and the high-temperature calcination treatment is calcination at 630° C. for 75 minutes.
[0024] The preparation method of the composite catalyst comprises the following steps: Step 1): Grind and mix rectorite, light calcium carbonate and anhydrous ethanol, add mercaptosuccinic acid and stir to mix, add a coupling agent and mix well, then heat the mixture, filter out the solid, vacuum dry and calcine to obtain a composite carrier; Step 2): After mixing the composite carrier, ethylene glycol and deionized water, add nickel nitrate hexahydrate and ammonium molybdate tetrahydrate, add ammonia water, heat and stir, cool to room temperature and centrifuge, wash three times with ethanol solution, vacuum dry and calcine to obtain a composite catalyst.
[0025] In step 1), the grinding and mixing is grinding at a speed of 420r / min for 45min; the stirring and mixing time is 42min; the heating treatment is stirring at a temperature of 52°C and a speed of 550r / min for 4.2h; the vacuum drying is drying at a temperature of 80°C to constant weight; the calcination is calcining at a temperature of 500°C for 3.2h; the mass ratio of the rectorite, light calcium carbonate, mercaptosuccinic acid, anhydrous ethanol and coupling agent is 8.2:0.07:0.25:31:3.3; and the coupling agent is a zirconium-aluminum coupling agent.
[0026] In step 2), the heating and stirring is performed at 200°C for 2.1 hours; the concentration of the ethanol solution is 70wt%; the calcination is performed at 410°C for 1.1 hours; the mass ratio of the composite carrier, ethylene glycol, deionized water, nickel nitrate hexahydrate, ammonium molybdate tetrahydrate and ammonia water is 21:72:20.5:0.65:2.5:10.5; and the concentration of the ammonia water is 24%.
[0027] Example 3
[0028] A treatment process for reducing sulfur content of calcined petroleum coke comprises the following steps: grinding the petroleum coke, sieving it, adding a composite catalyst, mixing it, and then calcining it at high temperature, and then cooling it to room temperature; In the treatment process, the screening is through a 60-mesh sieve; the mixing time is 35 minutes; and the high-temperature calcination treatment is calcination at 650° C. for 80 minutes.
[0029] The preparation method of the composite catalyst comprises the following steps: Step 1): Grind and mix rectorite, light calcium carbonate and anhydrous ethanol, add mercaptosuccinic acid and stir to mix, add a coupling agent and mix well, then heat the mixture, filter out the solid, vacuum dry and calcine to obtain a composite carrier; Step 2): After mixing the composite carrier, ethylene glycol and deionized water, add nickel nitrate hexahydrate and ammonium molybdate tetrahydrate, add ammonia water, heat and stir, cool to room temperature and centrifuge, wash three times with ethanol solution, vacuum dry and calcine to obtain a composite catalyst.
[0030] In step 1), the grinding and mixing is grinding at a speed of 450r / min for 50min; the stirring and mixing time is 45min; the heating treatment is stirring at a speed of 600r / min at a temperature of 55°C for 4.5h; the vacuum drying is drying at a temperature of 80°C to constant weight; the calcination is calcining at a temperature of 500°C for 3.5h; the mass ratio of the rectorite, light calcium carbonate, mercaptosuccinic acid, anhydrous ethanol and coupling agent is 8.5:0.07:0.3:32:3.3; and the coupling agent is a zirconium-aluminum coupling agent.
[0031] In step 2), the heating and stirring is performed at 200°C for 2.2 hours; the concentration of the ethanol solution is 70wt%; the calcination is performed at 410°C for 1.1 hours; the mass ratio of the composite carrier, ethylene glycol, deionized water, nickel nitrate hexahydrate, ammonium molybdate tetrahydrate and ammonia water is 22:75:21:0.7:2.6:11; and the concentration of the ammonia water is 24%.
[0032] Example 4
[0033] A treatment process for reducing sulfur content of calcined petroleum coke comprises the following steps: grinding the petroleum coke, sieving it, adding a composite catalyst, mixing it, and then calcining it at high temperature, and then cooling it to room temperature; In the treatment process, the screening is through a 60-mesh sieve; the mixing time is 38 minutes; and the high-temperature calcination treatment is calcination at 670° C. for 85 minutes.
[0034] The preparation method of the composite catalyst comprises the following steps: Step 1): Grind and mix rectorite, light calcium carbonate and anhydrous ethanol, add mercaptosuccinic acid and stir to mix, add a coupling agent and mix well, then heat the mixture, filter out the solid, vacuum dry and calcine to obtain a composite carrier; Step 2): After mixing the composite carrier, ethylene glycol and deionized water, add nickel nitrate hexahydrate and ammonium molybdate tetrahydrate, add ammonia water, heat and stir, cool to room temperature and centrifuge, wash three times with ethanol solution, vacuum dry and calcine to obtain a composite catalyst.
[0035] In step 1), the grinding and mixing is grinding at a speed of 470 r / min for 55 minutes; the stirring and mixing time is 48 minutes; the heating treatment is stirring at a speed of 650 r / min at a temperature of 58°C for 4.8 hours; the vacuum drying is drying at a temperature of 80°C to constant weight; the calcination is calcining at a temperature of 500°C for 3.8 hours; the mass ratio of the rectorite, light calcium carbonate, mercaptosuccinic acid, anhydrous ethanol and coupling agent is 8.8:0.08:0.35:34:3.4; and the coupling agent is a zirconium-aluminum coupling agent.
[0036] In step 2), the heating and stirring is performed at 200°C for 2.4 hours; the concentration of the ethanol solution is 70wt%; the calcination is performed at 415°C for 1.2 hours; the mass ratio of the composite carrier, ethylene glycol, deionized water, nickel nitrate hexahydrate, ammonium molybdate tetrahydrate and ammonia water is 23:78:21.5:0.75:2.7:11.5; and the concentration of the ammonia water is 24%.
[0037] Example 5
[0038] A treatment process for reducing sulfur content of calcined petroleum coke comprises the following steps: grinding the petroleum coke, sieving it, adding a composite catalyst, mixing it, and then calcining it at high temperature, and then cooling it to room temperature; In the treatment process, the screening is through a 60-mesh sieve; the mixing time is 40 minutes; and the high-temperature calcination treatment is calcination at 690° C. for 90 minutes.
[0039] The preparation method of the composite catalyst comprises the following steps: Step 1): Grind and mix rectorite, light calcium carbonate and anhydrous ethanol, add mercaptosuccinic acid and stir to mix, add a coupling agent and mix well, then heat the mixture, filter out the solid, vacuum dry and calcine to obtain a composite carrier; Step 2): After mixing the composite carrier, ethylene glycol and deionized water, add nickel nitrate hexahydrate and ammonium molybdate tetrahydrate, add ammonia water, heat and stir, cool to room temperature and centrifuge, wash three times with ethanol solution, vacuum dry and calcine to obtain a composite catalyst.
[0040] In step 1), the grinding and mixing is grinding at a speed of 500 r / min for 60 minutes; the stirring and mixing time is 50 minutes; the heating treatment is stirring at a temperature of 60°C and a speed of 700 r / min for 5 hours; the vacuum drying is drying at a temperature of 80°C to constant weight; the calcination is calcining at a temperature of 500°C for 4 hours; the mass ratio of the rectorite, light calcium carbonate, mercaptosuccinic acid, anhydrous ethanol and coupling agent is 9:0.08:0.4:35:3.4; and the coupling agent is a zirconium-aluminum coupling agent.
[0041] In step 2), the heating and stirring is performed at 200°C for 2.5 hours; the concentration of the ethanol solution is 70wt%; the calcination is performed at 420°C for 1.2 hours; the mass ratio of the composite carrier, ethylene glycol, deionized water, nickel nitrate hexahydrate, ammonium molybdate tetrahydrate and ammonia water is 24:80:22:0.8:2.8:12; and the concentration of the ammonia water is 24%.
[0042] Comparative Example 1 Compared with Example 3, the difference in Comparative Example 1 is that light calcium carbonate is not used, and the other components, preparation steps and parameters are the same.
[0043] Comparative Example 2 Compared with Example 3, Comparative Example 2 is different in that mercaptosuccinic acid is not used, and the remaining components, preparation steps and parameters are the same.
[0044] Comparative Example 3 Compared with Example 3, the difference of Comparative Example 3 is that the coupling agent in step 1) adopts aluminate coupling agent DL-411, and the other components, preparation steps and parameters are the same.
[0045] Comparative Example 4 Compared with Example 3, Comparative Example 4 is different in that no coupling agent is used in step 1), and the other components, preparation steps and parameters are the same.
[0046] The desulfurization rates of the petroleum cokes of Examples 1-5 and Comparative Examples 1-4 were calculated, and the test results are shown in Table 1.
[0047] Desulfurization rate (%) = (sulfur content in raw materials - sulfur content in calcined products) / sulfur content in raw materials 100%.
[0048] Table 1 Desulfurization rate (%) Example 1 86.5 Example 2 89.1 Example 3 87.7 Example 4 86.2 Example 5 87.4 Comparative Example 1 75.8 Comparative Example 2 70.6 Comparative Example 3 67.3 Comparative Example 4 57.8 From the test results in Table 1, it can be seen that compared with Comparative Examples 1-4, Examples 1-5 have a significant desulfurization effect on petroleum coke through the treatment process of the present invention.
[0049] The present invention forms a composite by rectorite and calcium carbonate to increase the number of active hydroxyl groups, and then allows mercaptosuccinic acid to adhere to the composite by physical adsorption on the surface of the composite. The introduced mercapto group can effectively improve the grafting rate of the composite to the zirconium-aluminum coupling agent. During the calcination process, the sulfur element of mercaptosuccinic acid is easily oxidized at high temperature, which accelerates the generation of aluminum / zirconium oxide and limits the growth of grains by coordination, so that smaller particles of zirconium / aluminum oxide can be uniformly generated on the surface of the composite. Calcium carbonate prevents the pores of the composite carrier from being blocked, which is beneficial to the generation of the porous structure of the composite carrier, thereby increasing the The specific surface area is increased, and the adsorption effect of the composite carrier is significantly improved, which is helpful for the removal of sulfur. When zirconium oxide and aluminum oxide are compounded on the surface of the composite carrier, the agglomeration phenomenon between the aluminum / zirconium oxide particles can be effectively reduced, so that aluminum oxide / zirconium oxide is evenly generated on the surface of the composite carrier. At the same time, the pore structure of the aluminum oxide / zirconium oxide layer can further increase the adsorption capacity of the composite carrier for active metal nickel / molybdenum. At the same time, the aluminum oxide / zirconium oxide layer can effectively increase the thermal stability of the rectorite, avoiding collapse caused by excessive calcination activation or calcination desulfurization.
[0050] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A process for reducing the sulfur content of calcined petroleum coke, characterized in that: The treatment process comprises the following steps: grinding the petroleum coke, sieving it, adding the composite catalyst, mixing it, and then calcining it, and then cooling it to complete; Wherein, the preparation method of the composite catalyst comprises the following steps: Step 1): Grind and mix rectorite, light calcium carbonate and anhydrous ethanol, add mercaptosuccinic acid and stir to mix, add a coupling agent and mix well, then heat the mixture, filter out the solid, vacuum dry and calcine to obtain a composite carrier; Step 2): After mixing the composite carrier, ethylene glycol and deionized water, add nickel nitrate hexahydrate and ammonium molybdate tetrahydrate, add ammonia water, heat and stir, cool to room temperature and centrifuge, wash with ethanol solution for multiple times, vacuum dry and calcine to obtain a composite catalyst.
2. A process for reducing sulfur content in calcined petroleum coke according to claim 1, characterized in that: In the treatment process, the screening is through a 50-100 mesh sieve; the mixing time is 30-40 minutes; and the calcination treatment is calcination at 620-690° C. for 70-90 minutes.
3. A process for reducing sulfur content in calcined petroleum coke according to claim 1, characterized in that: In step 1), the grinding and mixing is performed at a rotation speed of 400-500 r / min for 40-60 min; and the stirring and mixing time is 40-50 min.
4. A process for reducing sulfur content in calcined petroleum coke according to claim 1, characterized in that: In step 1), the vacuum drying is performed at 80° C. to a constant weight; the heating treatment is performed at 50-60° C. and 500-700 r / min with stirring for 4-5 hours.
5. A process for reducing sulfur content in calcined petroleum coke according to claim 1, characterized in that: In step 1), the mass ratio of the rectorite, light calcium carbonate, mercaptosuccinic acid, anhydrous ethanol and coupling agent is (8-9): (0.06-0.08): (0.2-0.4): (30-35): (3.2-3.4).
6. A process for reducing sulfur content in calcined petroleum coke according to claim 1 or 5, characterized in that: In step 1), the coupling agent is a zirconium-aluminum coupling agent; and the calcination is carried out at a temperature of 500° C. for 3-4 hours.
7. A process for reducing sulfur content in calcined petroleum coke according to claim 1, characterized in that: In step 2), the heating and stirring is heating at 200° C. for 2.0-2.5 hours; the concentration of the ethanol solution is 70 wt %.
8. A process for reducing sulfur content in calcined petroleum coke according to claim 1, characterized in that: In step 2), the calcination is carried out at a temperature of 400-420° C. for 1.0-1.2 h.
9. A process for reducing sulfur content in calcined petroleum coke according to claim 1, characterized in that: In step 2), the mass ratio of the composite carrier, ethylene glycol, deionized water, nickel nitrate hexahydrate, ammonium molybdate tetrahydrate and ammonia water is 20-24:70-80:20-22:0.6-0.8:2.4-2.8:10-12; the concentration of the ammonia water is 24%.
Citation Information
Patent Citations
Desulphurization method of petroleum coke
CN107384503A
Hydrotreating catalyst containing metal organic sulfides on doped supports
CN107645971A
Coking desulfurization method
CN111575039A
Petroleum coke desulfurization method based on iron-based oxygen carrier
CN113372938A
Technology for desulfurizing high-sulfur petroleum coke
CN116786034A